Correction of the Lower Lip With a Cartilage Graft and Lip Resection in Patients With Facioscapulohumeral Muscular Dystrophy. Issue 6 (September 2016) - Matsumoto, Mio; Onoda, Satoshi; Uehara, Hiroko; Miura, Yuki; Katayama, Yuko; Kimata, Yoshihiro
Abstract : Abstract: Facioscapulohumeral muscular dystrophy is an autosomal-dominant, slowly progressive myopathy that involves facial, shoulder, and upper arm muscles. Facial muscle atrophy and weakness leads to drooping of the lower lip, which has unfavorable functional and aesthetic outcomes. While there are several methods to correct drooping of the lower lip, including lip resection, free vascularized muscle transfer, and fascia suspension, there are no reports describing the use of an auricular cartilage graft to elevate the lip. The use of an auricular cartilage graft has several advantages, including a less invasive procedure and a longer-lasting effect. In this study, 3 patients with facioscapulohumeral muscular dystrophy underwent surgery involving an auricular cartilage graft with lip resection to sustain the lower lip, and satisfactory results were obtained. This procedure is simple and minimally invasive; thus, the authors believe that this is an appropriate technique to correct similar patients of lip deformity.